(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
The article analyzes the distribution, bioecological characteristics and development of the species Allium Costatovaginatum (Kamelin & Levichev) from the onion family. This plant (Russian name Luk rebristovlagolishniy) grows in the mountainous and sub-mountainous regions of Central Asia, including Uzbekistan, mainly on geophytic - gravelly and stony soils. This species is a perennial bulbous plant adapted to arid climatic conditions. Allium costatovaginatum, an endemic species, is analyzed according to scientific sources and field studies, its place among plant communities, its ecological and economic importance, its distribution area, and its potential as a natural resource. Information on the protection of the plant and its practical use in the future is provided. Allium costatovaginatum is a fennel plant, taking into account its ecological characteristics, its seed germination was studied in laboratory and soil conditions.